Poverty targeting in Asia - Weiss, John, 1948-; Asian Development Bank. Institute; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2005)
Following a comprehensive overview by the editor, this book offers a detailed assessment of the results of directly channelling resources to the poor and extensively discusses the experience of five Asian countries--India, Indonesia, the People's Republic of China, the Philippines and Thailand.
1. Experiences with poverty targeting in Asia : an overview / John Weiss -- 2. Poverty targeting in India / Pradeep Srivastava -- 3. Poverty targeting in Indonesia / Ari A. Perdana and John Maxwell -- 4. Poverty targeting in the People's Republic of China / Wang Sangui -- 5. Poverty targeting in Thailand / Peter Warr and Isra Sarntisart -- 6. Poverty targeting in the Philippines / Arsenio Balisacan and Rosemarie Edillon -- 7. Micro-finance and poverty reduction in Asia / John Weiss, Heather Montgomery and Elvira Kurmanalieva.
Five countries selected for study: India, Indonesia, the Peoples Republic of China, the Philippines, and Thailand.
Edited versions of papers presented at an Asian Development Bank Institute (ADBI) workshop in November 2003 and a conference in December 2003, both held in Tokyo.
"A joint publication of the Asian Development Bank Institute and Edward Elgar Publishing."
Includes bibliographical references and index.
Keywords: Poverty -- Asia -- Congresses; Poverty -- Pacific Area -- Congresses; Microfinance -- Asia -- Congresses; Microfinance -- Pacific Area -- Congresses; Asia -- Economic conditions -- 1945 -- Congresses; Pacific Area -- Economic conditions -- 20th century -- Congresses; Electronic books